Flexible optical fiber probe for surface roughness evaluation of internal channels in additively manufactured components - Subbarao, Guru Prasad Arudi (2018)
Recent developments in Additive Manufacturing (AM) has revolutionized the production capabilities of multitudes of aerospace components. However, being a stochastic process, there is minimal control over the surface quality and thus require adequate quality checks before implementation. In this context, this paper investigates a flexible optical fiber probe and speckle correlation measurements to quantitatively estimate the average surface roughness, Ra, of areas within internal channels. Details on probe design and preliminary measurement results on a comparator plate with Ra values varying between 6.3 μm and 25 μm are presented. The measurements are compared and validated using the Keyence optical tester (VR-3000).